Subjective experience of a depressive episode in bipolar affective disorder during wartime: a case report using the phenomenological interview method - RUDENKO, Sergii; DANYLIUK, Ivan; TASENKO, Mykhailo; TRAVERSE, Tetiana; LAZARIEVA, Anastasiia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. War, as a large-scale traumatic event, significantly impacts mental health, particularly intensifying affective disorders. Bipolar affective disorder (BAD), which follows a chronic course with mainly depressive symptoms, is especially susceptible to external stressors, including combat-related experiences. Psychiatric practice requires a clearer understanding of the subjective dimension of these conditions, especially when psychological trauma results from warfare. This study aims to present a clinical case of a depressive episode in a female patient with BAD living amid a full-scale military invasion, emphasizing a phenomenological analysis of her subjective experience. Methods. This study employed a comprehensive approach, incorporating clinical-anamnestic, clinical-psychopathological, psychodiagnostic, and catamnestic methods, as well as standardized psychometric tools (MOS SF-36, PCL-5, LEC-5, DASS-21). Additionally, a phenomenological interview was used to explore anomalous self-experience. Incorporating these methods allowed for a multidimensional assessment of the clinical course and the patient’s subjective experience. Results. Psychometric assessment revealed a high level of depressive symptoms, moderate anxiety, and a moderate decline in quality of life. Although the patient’s PCL-5 score did not surpass the threshold for PTSD diagnosis, the interview revealed several latent post-traumatic phenomena. Phenomenological analysis revealed a multidimensional structure of depressive experience, including disturbances in consciousness flow, loss of the ipseity of thought, short-term memory impairment, derealization, disorientation in time perception, episodic feelings of existential emptiness, and ambivalence. Notably, both somatic and cognitive anxiety symptoms were prominent. The patient also reported experiences of alienation from the world, a reduced sense of agency, and the feeling of being insufficiently "real" in social interactions. Conclusions. The study underscores the importance of using phenomenological interviews to explore anomalous self-experience as a tool for deepening the understanding of subjective experience in depressive episodes of BAD. The results demonstrate the necessity of a multidisciplinary approach to psychiatric diagnosis that includes both standardized assessment tools and qualitative exploration of the patient’s lifeworld. This clinical case further highlights the significance of war-related traumatization as a factor that not only exacerbates the clinical course of BAD but also profoundly transforms the subjective experience of mental illness. These findings open new perspectives for the development of personalized approaches to social and psychotherapeutic support strategies under conditions of mass trauma.